Mothers' perceptions of the UK physical activity and sedentary behaviour guidelines for the early years (Start Active, Stay Active): a qualitative study. Issue 9 (8th September 2015) - Bentley, Georgina F; Jago, Russell; Turner, Katrina M
Abstract : Objectives: Higher levels of physical activity (PA) during early childhood have been associated with improved health outcomes, whereas sedentary behaviour (SB) has been associated with poorer health outcomes in children. In 2011, the UK produced guidelines for PA and SB in children under 5 years. Mothers have been identified as key influences in young children's PA and SB. The aim of this study was to use in-depth interviews with mothers of preschool children to examine attitudes to the guidance. Design: Qualitative study using one-to-one, semistructured interviews; Data were analysed thematically using a framework approach. Setting: Mothers were recruited from preschools, nurseries, and mother and toddler groups located in four areas of varying socioeconomic status within Bristol, UK. Participants: 24 mothers who were considered the main or joint carer for a preschool child who was at least 2 years of age but had not yet started formal schooling. Results: Mothers are not aware of the UK PA and SB guidelines for the early years. They believe that their child achieves the guideline targets for PA and SB and therefore, they do not believe these quidelines are relevant to them. Mothers feel that an increase in PA and reduction in SB (especially screen-viewing) would cause stress for mothers. Mothers found defining and quantifying PA and SB in their preschool child problematic. Conclusions: As mothers do not identify with the need to increase PA or reduce SB in their child, awareness of the guidelines alone is unlikely to initiate behaviour change. Information on how mothers can make a more accurate assessment of their preschool child's PA and SB levels, and information about the benefits of increased PA and reduced SB should be provided alongside the guideline targets. Clear messages need to be developed that reframe the guidelines into pragmatic and usable targets.